Selection and Characterization of DNA Aptamers for Constructing Aptamer-AuNPs Colorimetric Method for Detection of AFM1 - Ruobing Liu; Fuyuan Zhang; Yaxin Sang; Minxuan Liu; Minghui Shi; Xianghong Wang (Foods, 2022)
Aflatoxin M1 (AFM1), one of the most toxic mycotoxins, is a feed and food contaminant of global concern. To isolate the ssDNA aptamer of AFM1, synthesized magnetic graphene oxide nanomaterials, 12 rounds of subtractive systematic evolution of ligands by exponential enrichment (SELEX) selection were carried out. As a result, 24 candidate aptamers were selected, and their sequence similarity exceeded 97%. Their binding affinity and specificity were further examined by fluorescence and biofilm interferometry (BLI) methods. One aptamer (Apt-5) against AFM1 with a high affinity and specificity was isolated and demonstrated to be the optimal aptamer, whose dissociation constant reached the nanomolar level, Kd = 8.12 ± 1.51 nM. Additionally, molecular docking studies were used to predict the possible binding sites and mechanisms of the two. Based on Apt-5, an unlabeled aptamer-AuNPs colorimetric method was established to detect AFM1 in milk with a linear range of 0.078–10 ng/mL, and the actual detection limit was 0.078 ng/mL. These results demonstrated that this detection technique could be useful for the quantitative determination of AFM1 in milk and dairy products.